The Factors of Stockpiling Behavior Using Health Belief Model With Moderating Role of Perceived Scarcity in Context of Covid-19 - Marcellina Elfrida Laksmana; Ferrel Enoch Ibrahim; Adela Diovany; Evi Rinawati Simanjuntak (Universitas Negeri Semarang, 2023)
The COVID-19 pandemic that occurred made people panic and do all kinds of ways to avoid getting infected with COVID-19. One of the ways to avoid getting infected is by stockpiling health products because it requires certain health products to avoid getting infected. Due to the lack of research on COVID-19 related to perceived susceptibility, perceived severity, perceived barriers, stockpiling, and perceived scarcity, this research was created with the aim that business owners and governments can take action and make appropriate regulations when a pandemic occurs again in the future. will come. This study involved 300 respondents and was examined using a quantitative non-probability convenience sampling approach with the Smart PLS application to test the validity, reliability, and hypotheses. The results of this study explain that perceived susceptibility, perceived severity, and perceived barriers have a positive relationship with stockpiling, and perceived scarcity moderates the relationship between perceived severity and stockpiling.